2022
DOI: 10.3390/d14090735
|View full text |Cite
|
Sign up to set email alerts
|

13C-Labeled Artificial Root Exudates Are Immediately Respired in a Peat Mesocosm Study

Abstract: Globally, peatlands have been recognized as important carbon sinks while only covering approximately 3% of the earth’s land surface. Root exudates are known key drivers of C cycling in soils and rhizosphere priming effects have been studied extensively in terrestrial ecosystems. Their role for decomposition of peat still remains unclear, as little research about their fate and potential priming effects in peat exists. In this study, we aimed to evaluate pathways of root exudates and their short-term priming ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Leiber‐Sauheitl et al 54 found no significant priming (no priming at all or insignificant negative priming) in organic soil used for grazing after an addition of isotopically labelled sheep excrements. More recently, Müller et al 33 found no noticeable priming in nutrient‐poor bog peat after addition of artificial root exudates, and Aaltonen et al 32 found no priming after glucose addition and water table manipulation in an incubation experiment with peat collected from clear‐cut and forested peatlands. These results are in accordance with results presented here as well as with previous results of the same peat soils utilizing a natural abundance ( 14 C) approach 36 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Leiber‐Sauheitl et al 54 found no significant priming (no priming at all or insignificant negative priming) in organic soil used for grazing after an addition of isotopically labelled sheep excrements. More recently, Müller et al 33 found no noticeable priming in nutrient‐poor bog peat after addition of artificial root exudates, and Aaltonen et al 32 found no priming after glucose addition and water table manipulation in an incubation experiment with peat collected from clear‐cut and forested peatlands. These results are in accordance with results presented here as well as with previous results of the same peat soils utilizing a natural abundance ( 14 C) approach 36 …”
Section: Discussionmentioning
confidence: 99%
“…In this study we found a negative PE in peat soils from two different study sites with different nutrient status: the added 13 C-glucose simulating in a simplified manner fresh photosynthates and leachates into the soil did not increase the decomposition of the old SOM in these peat soils, but on the contrary, decreased it. Studies of PE in organic soils are still inadequate and contradictory; both positive (e.g., 12,30,34,37,52,53 ) and negative priming (e.g., 12,29,31,37 ), as well as observations without significant priming (e.g., 32,33,36,37,54 ) have been reported. These results suggest that the factors behind PE are complicated and depend on various variables, such as the humification rate, C and N content, substrate type and concentration, microbial communities, soil moisture or water table level.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations